PEMBUATAN PUPUK FERMENTASI CAIR BERBASIS LIMBAH VINASSE - Astuti, Widi; Mahatmanti, Widhi (Rekayasa : Jurnal Penerapan Teknologi dan Pembelajaran, 2017)
Vinasse waste, which is a by-product of the alcohol industry, has polluted the rice field en- vironment in the Bekonang, Sukoharjo and surrounding villages. This problem arises into the realm of law with the publication of a law on alcohol which prohibits low-level alcohol producers to sell to the public. This regulation increasingly discourages alcoholic craftsmen who are mostly used as raw materials in herbal and medicinal industries. In addition to the narrower marketing, they are also confronted by farmers who are angered by the environmental pollution of vinasse waste that for decades has only been dumped into irrigation flows without treatment. Field observations and preliminary studies on vinasse waste content found no harmful ingredients to the environment ex- cept high acidity (4.5). The rest is the content of organic materials that can be utilized to fertilize the soil. Therefore waste alcohol should be processed with the addition of complementary organic materials to be used as a medium to grow probiotic bacteria that are very good for soil and plants. This activity is intended to provide education on how to process waste vinasse into liquid fermen- tation  fertilizer  that  can  be  utilized  by  local  residents  and  society  in  general.  Activity  method that will be done is socialization about potential waste vinasse, making waste processing equip- ment,  giving  skill  to  make  liquid  fermentation  fertilizer  and  applying  it  to  cassava  plant  land. These  activities  are  expected  to  generate  positive  perception  changes  and  increase  knowl- edge of craftsmen and farmers in addressing vinasse waste issues. In addition, both parties are able  to  treat  the  harmful  waste  into  probiotic  bacteria  and  fertilizer  products  with  high  qual- ity. With this activity, the source of conflict of Bekonang village community will decrease slow- ly along with the socialization of the results of the activity to the wider community and the as- sistance  of  the  village  government  as  the  administrative  responsibility  of  Bekonang  village